THE INFLUENCE OF PRODUCT QUALITY AND CONSUMER BEHAVIOR ON THE PURCHASE DECISION OF RANTI PRODUCTS IN DEPOK - Riyanti, Agustin (JURNAL KAJIAN ISLAM MODERN, 2025)
This research aims to identify how product quality and consumer behavior can influence purchasing decisions for Ranti products, as well as how the two interact in the local market context. The research subjects consisted of consumers of Ranti products who live in Depok, who were selected using a purposive sampling technique. The method used in this research is a quantitative approach using surveys as a data collection tool. The collected data was analyzed using regression analysis techniques to measure the influence between product quality variables, consumer behavior and purchasing decisions. The research results show that product quality has a positive influence on purchasing decisions, while consumer behavior which is influenced by social and psychological factors also has a significant influence. In addition, there is a mutually reinforcing relationship between product quality and consumer behavior in influencing purchasing decisions. This shows the importance of integration between product quality and understanding consumer behavior to design more effective marketing strategies and contributes to marketing theory by integrating two important factors in purchasing decisions in local markets, namely product quality and consumer behavior. These findings are also useful for producers in designing marketing strategies that can attract more consumers and increase the competitiveness of Ranti products in the market.